Five‐year experience with pulmonary vein isolation using the second‐generation cryoballoon for treatment of persistent atrial fibrillation. (5th October 2018) - Akkaya, Ersan; Berkowitsch, Alexander; Zaltsberg, Sergej; Greiss, Harald; Hamm, Christian W.; Sperzel, Johannes; Neumann, Thomas; Kuniss, Malte
Abstract: Introduction: We analyzed the procedural experience and clinical outcome after pulmonary vein isolation (PVI) in patients with persistent atrial fibrillation (AF) gained over 5 years using the second‐generation cryoballoon (CB‐Adv). Methods and Results: For this retrospective study, we enrolled 281 patients undergoing PVI at our institution between 2012 and 2016. The analyzed period was divided into 5 calendar years. Follow‐up data, including Holter electrocardiography recordings, were collected during outpatient clinic visits. The impact of several variables on outcome was evaluated by means of univariate and multivariate analyses and Cox proportional hazards regression models. The median procedure and fluoroscopy times over the years were 90 (72 of 114) and 15 (11 of 21) minutes, respectively. A continuous decline in complication rates and fluoroscopy and procedure times was observed in each subsequent year. During mid‐term follow‐up (33 [25 of 48] months), 178 (63.3%) patients were AF, atrial flutter, or atrial tachycardia free. Multivariate analysis revealed left atrial area (hazard ratio [HR] = 1.05; P < 0.001), female sex (HR = 2.53; P < 0.001), and common ostium (HR = 1.93; P < 0.001) as significant predictors of outcome. The overall 1‐year success rate was 76.2%. A gradual decrease in the 1‐year success rate (from 90.5% in 2012 to 67.9% in 2016) was mainly related to a steady increase of left atrial area in the entire cohort with successive years of the study. Conclusions: PVI using CB‐Adv in patients with persistent AF is accompanied by a learning curve and facilitates a satisfactory outcome, followed by the proper selection of patients.